Preferensi Pemilih Muslim Milenial pada Pemilihan Presiden-Wakil Presiden 2019 - Jubba, Hasse; Iribaram, Suparto; Pabbajah, Mustaqim; Elizabeth, Misbah Zulfa (JSW (Jurnal Sosiologi Walisongo), 2019)
This paper discusses the issue of the tendency to vote of millennial Muslim voters in presidential-vice presidential elections 2019. This issue is answered through three questions. Applying mix-methods of quantitative and qualitative, the data was obtained through surveys and interviews as well as literature studies. The results were analyzed using a descriptive-analytical analysis. These results of this research show three important things. First, millennial Muslim voters in the presidential-vice presidential election 2019 tend to choose civilians as potential leaders. Civilians are considered capable of overcoming problems and can advance Indonesia in the future. Second, there are variations in the reasons for voters voting their candidates. In addition to performance factors, firmness and competency factors are the drivers for voters to make choices regarding contending candidates. Third, differences in political choices have an impact on polarization among Muslim communities. Different choices lead to new groupings in Muslim societies and even tend to emerge hates and dislikes from each other.